Impact of Covid-19 Pandemic on Food Consumption in Indonesia - Amalia Zaida (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
Prevention of Covid-19 transmission by increasing immunity of the body with protein intake results in changes in people's dietary behavior. Pressure due to changing environment and loss of work leads to the tendency to eat sweet foods, preserved, high in fat and salt. This study aims to determine changes in food consumption patterns in Indonesia during the Covid-19 pandemic. Use a quick assessment of empirical facts about Indonesia's ongoing impact on Covid-19. The research approach framework conceptualizes Covid-19 as a 'Cause', and its effect on changes in food consumption patterns is